Operation Thunderbolt : Flight 139 and the raid on Entebbe Airport, the most audacious hostage rescue mission in history /: Flight 139 and the raid on Entebbe Airport, the most audacious hostage rescue mission in history. (2015) - David, Saul, 1966-
No abstract available